Intraoperative tumor localization using a titanium ring strip in totally laparoscopic distal gastrectomy for middle-third gastric cancer - Jae-Kyun Park; Chang-In Choi; Tae Yong Jeon; Hyuk Jae Jung; Si Hak Lee; Sun Hwi Hwang; Dae-Hwan Kim (Kosin Medical Journal, 2023)
Background This study presents a novel technical tip for intraoperative tumor localization and determination of the proximal resection line using a titanium ring strip for totally laparoscopic distal gastrectomy in patients with middle-third gastric cancer and describes the short-term results of its application. Methods In total, 42 patients with middle-third gastric cancer who underwent intraoperative tumor localization using a titanium ring strip and determination of the proximal resection line through intraoperative radiography between January 2020 and December 2021 were enrolled in this study. We retrospectively analyzed patients’ prospectively collected clinical, pathological, and surgical data. Results Twenty-six men and 16 women with a mean age of 58.3±12.5 years were enrolled. The mean operation time and estimated blood loss were 212.6±43.0 minutes and 122.4±77.6 mL, respectively. The lengths of the proximal and distal resection margin were 2.0±0.4 cm (range, 0.8–3.7 cm) and 10.5±4.1 cm (range, 0.4–20.4 cm), respectively. Roux-en-Y anastomosis was performed in 30 patients, while Billroth II with Braun anastomosis was performed in 12 patients. There were no procedure-related complications, and the mean postoperative hospital stay was 7.2±1.9 days. For all patients, the negative proximal resection margin was confirmed by postoperative pathological examinations. Conclusions Intraoperative tumor localization and determination of the proximal resection line using a titanium ring strip is a useful alternative method that can be easily and safely performed. This method is especially useful for patients with middle-third gastric cancer requiring an appropriate proximal resection margin.